Sustainability conditions of Polish agriculture in the context of the use of plant protection products, as compared to other European Union countries. Economic aspects - Marek Zieliński; Arkadiusz Zalewski; Sylwia Łaba (Journal of Plant Protection Research)
Sustainable agriculture is a management system based on the use of agricultural practices that contribute to maintaining the natural environment in good condition. It allows for the rational use of its resources, and minimizing losses for society while maintaining profitability of agricultural production. An important feature of a sustainable agricultural system is the moderate use of industrial agricultural production products, including plant protection products, which in practice should be closely matched to the type and strength of the threat occurring in agricultural crops. The cost of plant protection products per 1 ha of crops is an important indicator of the intensity of agricultural production, which as a result of growing competitive pressure, is still increasing, especially in areas with favorable natural conditions for its development. In this context, it is therefore important to emphasize the strong current aim and readiness of the European Union (EU) to restrict the use of plant protection products in agriculture. This is referred to as the “farm to fork” strategy, which is an important element of the European Green Deal. Currently, the European Commission (EC) is taking a number of legislative steps to reduce the overall use of plant protection products. However, the question arises whether and to what extent Polish agriculture can participate in the ambitious EU goal to reduce them. To try to answer this question, an assessment was made of the amounts and structure of the consumption of chemical plant protection products in Poland, and compared to other EU countries. It was also important to compare the costs of plant protection products per 1 ha of crops on farms in Poland, with similar farms in other European Union countries, while taking into consideration the diverse natural farming conditions in which they operate.